2021
DOI: 10.3389/fpsyt.2021.660746
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Interaction Effects of Gender Contentedness and Pubertal Timing on Adolescent Longitudinal Psychological and Behavioral Health Outcomes

Abstract: Background: Off-time pubertal timing (PT) and non-conforming gender identity have been reported to predict adverse health and well-being in adolescents. However, the joint effects of these two factors are less addressed. We aimed to investigate the main and interaction effects of gender identity, proxied by perceived gender contentedness (GC), and PT on longitudinal adolescent psychological and behavioral outcomes.Methods: Data (N = 1806, Mage = 13.3 ± 0.5 years) come from the Taiwan Youth Project, which prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
2
4
1
Order By: Relevance
“…Our study did not find strong evidence for an association between early timing of menarche and depressive symptoms in adulthood, which was consistent with a recent umbrella review (Lee et al, 2022) and prospective (Boden et al, 2011;Gaysina et al, 2015;Goering and Mrug, 2022;Kuo et al, 2021;Natsuaki et al, 2009;Opoliner et al, 2014;Senia et al, 2018), and retrospective studies (Herva et al, 2004;Kim et al, 2023). However, this finding was inconsistent with other prospective studies (Copeland et al, 2010;Graber et al, 2004;Mendle et al, 2018) and a retrospective study, which report evidence of a persisting effect into adulthood (Beltz, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Our study did not find strong evidence for an association between early timing of menarche and depressive symptoms in adulthood, which was consistent with a recent umbrella review (Lee et al, 2022) and prospective (Boden et al, 2011;Gaysina et al, 2015;Goering and Mrug, 2022;Kuo et al, 2021;Natsuaki et al, 2009;Opoliner et al, 2014;Senia et al, 2018), and retrospective studies (Herva et al, 2004;Kim et al, 2023). However, this finding was inconsistent with other prospective studies (Copeland et al, 2010;Graber et al, 2004;Mendle et al, 2018) and a retrospective study, which report evidence of a persisting effect into adulthood (Beltz, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…A majority of adolescents (78%) indicated to never experience any gender non-contentedness. This is mostly in line with existing literature, which found that 87% of a sample of Taiwanese junior high school students were satisfied with their gender and that 90% of a sample of 9-10-year-olds from the Unites States never reported a wish to be of the other gender (Kuo et al, 2021;Potter et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, in the current sample we found that a relatively large percentage (19%) of young adolescents reported gender non-contentedness in adolescence, but not in early adulthood. This is a larger percentage than found by Kuo et al’s ( 2021 ) study, who reported a group (8% of 1806 children) who experienced gender dissatisfaction around age 13, but not anymore around age 22. The larger percentage of individuals with temporary, declining gender dissatisfaction in our sample might be explained by the wider age range (11–26 years) of the TRAILS sample.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations